Comparison of Serum Zinc Levels among Children with Simple Febrile Seizure and Control Group: A Systematic Review - NASEHI, Mohammad Mehdi; SAKHAEI, Roya; MOOSAZADEH*, mahmood; ALIRAMZANY, Maryam (Iranian Journal of Child Neurology, 2015)
<!--[if gte mso 9]> <![endif]--> How to Cite This Article: Nasehi MM, Sakhaei R, Moosazadeh M, Aliramzany M. Comparison of Serum Zinc Levels among Children with Simple Febrile Seizure and Control Group: A Systematic Review. Iran J Child Neurol. 2015 Winter;9(1):17-24 . Abstract Objective Several factors are involved in the etiology of febrile seizure (FS), among them is zinc (Zn), which has been discussed in various studies. The present systematic review compares Zn levels in children with FS and a control group. Materials & Methods We searched keywords of febrile seizure, febrile convulsion, children, childhood, fever, trace elements, risk factor, predisposing, zinc, Zn, and epilepsy in the following databases: SCOPUS, PubMed, and Google Scholar. The quality of research papers was assessed using a checklist. Data was extracted from primary studies based on demographic variables and amounts of Zn in case and control groups. Results Twenty primary studies were entered in the present study. Of which, eighteen studies, reported that Zn serum levels were significantly lower in the case group (patients with FS) than the control group. Conclusion The present systematic review indicated that Zn is one factor for predicting FS. A low level of this element among children can be regarded as a contributing factor for FS, a conclusion with a high consensus among different studies carried out in different parts of the world. References Heydarian F, Ashrafzadeh F, Ghasemian A. Serum ZINC level in Patients with simple febrile seizure. Iran J Child Neurology 2010; 14(2):41-44. Mahyar A, Pahlavan AA, Varasteh-Nejad A. Serum zinc level in children with febrile seizure. Acta Medica Iranica 2008; 46(6): 477-80. Kunda GK, Rabin F, Nandi ER, Sheikh N, Akhter S. Etiology and Risk Factors of Febrile Seizure – An Update. Bangladesh J Child Health 2010; 34 (3):103-112. Abbaskhaniyan A, Shokrzadeh M, Rafati MR, Mashhadiakabr M, Arab A, Yazdani J. Survey and Relation of Serum Magnesium Level in Children with Seizure. J Mazand Univ Med Sci 2012; 2(90): 43-49. Abaskhanian A, Vahid Shahi K, Parvinnejad N. The Association between Iron Deficiency and the First Episode of Febrile Seizure. J Babol Univ Med Sci 2009; 11(3):32-36. Amiri M, Farzin L, Moassesi ME, Sajadi F. Serum Trace Element Levels in Febrile Convulsion. Biol Trace Elem Res 2010; 135:38–44. Fetveit A. Assessment of febrile seizures in children. Euro J Pedia 2008; 167:17-27. Sadeghzadeh M, Khoshnevis P, Mahboubi E. Iron Status and Febrile Seizure- A Case Control Study in Children Less Than 3 Years. Iran J Child Neurol 2012; 6(4):27-31. Salehiomran MR, Mahzari M. Zinc Status in Febrile Seizure: A Case-Control Study. Iran J Child Neurol. 2013; 7(4):20-23. Shiva S, Barzegar M, Zokaie N, Shiva Sh. Dose Supplemental Zinc Prevents Recurrence of Febrile Seizures?. Iran J Child Neurol 2011; 5(4):11-14. Sadeghzadeh M, Khoshnevis Asl P, Mousavinasab N, Koosha A, Norouzi M. The Relation Between Serum Zinc Level and Febrile Seizures in Children Admitted to Zanjan Valie-Asr Hospital. ZUMS Journal 2011; 19 (74):17-24. Waruiru C, Appleton R. febrile seizures: an update. Archive Dis Child 2004; 89: 751-6. Moosazadeh M, Nekoei-moghadam M, Emrani Z, Amiresmaili M. Prevalence of unwanted pregnancy in Iran: A systematic review and meta-analysis. Int J Health Plann Mgmt, 2013; Published online in Wiley Online Library, DOI: 10.1002/hpm.2184. available at: http://onlinelibrary.wiley.com/journal/10.1002/%28ISSN%291099-1751/earlyview. Elm EV, Altman DG, Egger M, Pocock SJ, Gotzsche PC, Vandenbroucke P, et al. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement: guidelines for reporting observational studies. Preventive medicine 2007; 45(4): 247-251. Shea BJ, Grimshaw JM, Wells GA, Boers M, Andersson N, Hamel C, et al. Development of AMSTAR: a measurement tool to assess the methodological quality of systematic reviews. BMC medical research methodology 2007; 7(1):10. Garty BZ, Olomucki R, Lerman-Sagie T, Nitzan M. Cerebrospinal fluid zinc concentration in febrile children’s. Arch Dis Child 1995; 73(4):338-41. Papierkowski A, Mroczkowska-Juchkiewics A, Pawlowska KA, Pasternak K. Magnesium and zinc levels in blood serum and cerebrospinal fluid in children with febrile convulsions. Pol Merkuriusz Le 1999; 6(33): 138-40. Burhanoglu M, Tutuncuoglu S, Coker C, Tekgul H, Ozgur T. Hypozincemia in febrile convulsion. Eur J Pediatr 1996; 155(6):498-501. Kumar L, Chaurasiya OS, Gupta AH. Prospective Study of Level of Serum Zinc In Patients of Febrile Seizures, Idiopathic Epilepsy, and CNS Infections. People’s Journal of Scientific Research 2011; 4(2):1-4. Palliana RR, Singh DK, Borade A. ZINC deficiency as a risk factor febrile seizure. Pediatrics 2008; 121(2):358-365. Ehsanipour F, Talebitaher M, Vahid Harandi N, Kani K. Serum Zinc Level in Children with Febrile Convulsion and its Comparison with that of Control Group. Iran J Pediatr 2009; 19)1):65-68. Kafadar I, Akıncı AB, Pekun F, Adal E. The Role of Serum Zinc Level in Febrile Convulsion Etiology. J Pediatr Inf 2012; 6: 90-93. Lee JH, Kim JH. Comparison of Serum Zinc Levels Measured by Inductively Coupled Plasma Mass Spectrometry in Preschool Children with Febrile and Afebrile Seizures. Ann Lab Med 2012; 32:190-193. Margaretha L, Masloman N. Correlation between serum zinc level and simple febrile seizure in children. Paediatr Indones 2010; 50(6): 326-330. Mollah MAH, Rakshit SC, Anwar KS, Arslan MI, Saha N, Ahmed S, et al. Zinc concentration in serum and cerebrospinal fluid simultaneously decrease in children with febrile seizure: Findings from a prospective study in Bangladesh. Acta Pædiatrica 2008; 97:1707–1711. Mollah MAH, Ranjan DP, Tarafdar SA, et al. Zinc in CSF of patients with febrile convulsion. Ind J Pediatr 2002; 69: 859-61. Modarresi MR, Shahkarami SMA, Yaghini O, Shahbi J, Mosaiiebi D, Mahmoodian T. The relationship between Zinc deficiency and Febrile Convulsion in Isfahan, Iran. Iran J Child Neurology 2011; 5(2):27-31. Tutuncuoglu S, Kutukculer N, Kepe L, Coker C, Berdeli A, Tekgul H. Proinflammatory cytokines, prostaglandins and zinc in febrile Convulsions. Pediatrics International 2001; 43: 235–239. Talebian A, Vakili Z, Talar SA, Kazemi SM, Mousavi GA. Assessment of the Relation between Serum Zinc & Magnesium Levels in Children with Febrile Convulsion. Iranian Journal of Pathology 2009; 4 (4), 157 – 160. Gunduz Z, Yavuz I, Koparal M, Kumandas S, Saraymen R. Serum and cerebrospinal fluid zinc level in children with febrile convulsion. Acta Paediatr Jpn 1996; 38(3): 237-41. Cho WJ, Son BH, Kim SW. Levels of Sodium and Zinc Concentration in Febrile Convulsion. J Korean Child Neurol Soc 1999; 7(2):214-219. Cho HS, Shin JH, Seo JY, Lee CA, Kim SH, Chae KY. The Levels of Zinc and Neuron-specific Enolase in Febrile Convulsion. Korean J Pediatr 2004; 47(10):1087-1092. Ganesh R, Janakiraman L, Meenakshi B. Serum zinc levels are low in children with simple febrile seizures compared with those in children with epileptic seizures and controls. Ann Trop Paediatr 2011; 31(4):345-9. Ganesh R, Janakiraman L. Serum zinc levels in children with simple febrile seizure. Clin Pediatr (Phila) 2008; 47(2):164-6. Okposio MM, Sadoh WE, Ofovwe GE, Onyiriuka AN. Serum zinc level in Nigerian children with febrile convulsion. Journal of Pediatric Neurology 2012; 10(3):187-191. Itoh M, Ebadi M. The selective inhibition of hippocampal glutamic acid decarboxylase in zinc induced epileptic seizures. Neurochem Res 1982; 7(10): 1287-98. Peters S, Koh J, Choi W. Zinc selectively blocks the action of N-methyl-D-aspartate on cortical neurons. Science 1987; 236 (4801): 589-93. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->